ARID1A and CEBPα cooperatively inhibit UCA1 transcription in breast cancer. Issue 45 (8th November 2018) - Guo, Xiao; Zhang, Yin; Mayakonda, Anand; Madan, Vikas; Ding, Ling-Wen; Lin, Le-Hang; Zia, Saadiya; Gery, Sigal; Tyner, Jeffrey; Zhou, Wu; Yin, Dong; Lin, De-Chen; et al.
Abstract As one of the primary members of SWI/SNF chromatin remodeling complexes, ARID1A contains frequent loss-of-function mutations in many types of cancers. However, the molecular mechanisms underlying ARID1A deficiency in cancer biology remain to be investigated. Using breast cancer as a model, we report that silencing ARID1A significantly increased cellular proliferation and migration. Mechanistically, primarily functioning as a transcriptional repressor, loss of ARID1A profoundly alters histone modifications and the transcriptome. Notably, ARID1A inhibited the expression of a long non-coding RNA, UCA1, by regulating chromatin access of the transcription factor CEBPα. Restoration experiments showed thatUCA1 mediates the functions of ARID1A that induces loss of cellular proliferation and migration. Together, our findings characterizeARID1A as a key tumor-suppressor gene in breast cancer through cooperation withCEBPα, and loss-of-function mutations of ARID1A activates UCA1.